COI-Based DNA Barcoding of Selais Fish from Arut River, Central Kalimantan, Indonesia - Tomi Kasayev; Tuty Arisuryanti (Universitas Gadjah Mada, 2022)
Selais fish belongs to the family Siluridae consisting of 12 genera with 104 properly validated species. The human need for these fish has sharply increased due to the benefits provided, especially for consumption. However, morphologically the selais fish are slightly challenging to differentiate among other silurid fish for non-specialist experts. Thus, a DNA barcoding approach using the mitochondrial COI gene as a molecular marker in this study was applied to clarify a taxonomic position and classification species of selais fish from Arut River (Central Kalimantan, Indonesia) and was also to assembly fish COI database storage from Indonesia. In this research, the method used was a PCR (Polymerase Chain Reaction) method with a pair of universal barcoding primers, FishF2 and FishR2. Based on partial COI fragment-based DNA barcoding, the whole samples showed no sequence differences (only 1 haplotype) within the population and this confirmed that these fish only consisted of one identical species. Furthermore, phylogenetic analysis (NJ / ML / BI) revealed that selais fish in this study had a close genetic relationship with Ompok hypophthalmus compared to other Ompok groups. This relationship was supported by the genetic distance value not exceeding 3.6% and this evaluated the undetermined naming of the selais fish from Arut River which was previously still unclassifiable.